Perancangan Sistem Informasi Penjualan dan Persediaan Sparepart Mobil Pada PD Jaya Buana Motor - Devi; Jasmir; Aryani, Lies (LPPM STIKOM Dinamika Bangsa, 2023)
Jaya Buana Motor is a trading business engaged in the sale of car spare parts. the sales and inventory transaction system owned by Jaya Buana Motor is still manual by making notes in the agenda book and also using cash notes. So that it causes problems that occur, the store has difficulty in recaping sales data, it is difficult to know the amount of stock quickly and accurately, errors in recording sales transactions occur frequently, and there are missing notes. This study aims to analyze the system that is running at Jaya Buana Motor Jambi in order to find out existing problems and find solutions and design a sales and inventory information system that helps record spare parts sales transactions to report reports. The research uses the PHP programming language, MySQL database and the waterfall system development method. This research has stages, namely problem identification, literature study, data collection, system analysis, system development and reporting of research results. The results of this system design can help Jaya Buana Motor Jambi in recording sales transactions to reporting reports, and can minimize the occurrence of calculation errors.